PENINGKATAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB MELALUI KEBIJAKAN MERDEKA BELAJAR DALAM PEMBELAJARAN IPS - Tarisa Celin (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of this study are: 1) to explain how the efforts of IPS teachers in improving the character of discipline and responsibility through the policy of freedom of learning in social learning class 7.10 in SMPN 3 Tulungagung; 2) to explain the form of improving the character of discipline and responsibility through the policy of freedom of learning in social learning students grade 7.10 in SMPN 3 Tulungagung; and 3) to describe the supporting and inhibiting factors of increasing the character of discipline and responsibility through the policy of freedom of learning in students grade 7.10 in SMPN 3 Tulungagung. This research was conducted in May 2022 which was held in class 7.10 SMPN 3 Tulungagung. This study uses qualitative descriptive methods. Researchers use data collection techniques with observation, interviews and documentation to answer the focus of research. The data analysis used is Miles and Huberman. Namely data collection, data presentation, data reduction and conclusions made until the data is saturated. Informants in this study are the principal of SMPN 3 Tulungagung, vice principal for curriculum, social studies teacher class 7.10, and students class 7.10. The results showed the efforts of teachers in improving the character of discipline and responsibility to students in class 7.10 through the policy of freedom of learning in social studies, namely: 1) become an exemplary figure for students; 2) always prioritize class agreements; 3) implement lesson plans that contain character values, interesting, student-centered; 4) always reflect at the end of the lesson; and 5) establish good communication with students and guardians. The improvement of discipline and responsibility character in grade 7.10 students can be seen in several things such as the arrival of students, the implementation of class pickets, the use of uniforms neatly, the granting of permits when not entering. While the supporting factors in the increase include: the establishment of good communication between the teacher and the teacher or the teacher with the principal, a positive school environment, family environment, motivation in learning. While the inhibiting factors are: on the part of the parents, the lack of good collaboration between teachers. Abstrak Tujuan dari penelitian ini adalah: 1) untuk menjelaskan bagaimana upaya guru IPS dalam meningkatkan karakter disiplin dan tanggung jawab melalui kebijakan merdeka belajar dalam pembelajaran IPS kelas 7.10 di SMPN 3 Tulungagung; 2) untuk menjelaskan bentuk peningkatan karakter disiplin dan tanggung jawab melalui kebijakan merdeka belajar dalam pembelajaran IPS siswa kelas 7.10 di SMPN 3 Tulungagung; dan 3) untuk mendeskripsikan faktor pendukung dan penghambat peningkatan karakter disiplin dan tanggung jawab melalui kebijakan merdeka belajar pada siswa kelas 7.10 di SMPN 3 Tulungagung. Penelitian ini dilakukan pada bulan Mei 2022 yang bertempat di kelas 7.10 SMPN 3 Tulungagung. Penelitian ini menggunakan metode deskriptif kualitatif. Peneliti menggunakan teknik pengumpulan data dengan kegiatan observasi, wawancara serta dokumentasi untuk menjawab fokus penelitian. Analisis data yang digunakan adalah Miles dan Huberman. Yaitu pengumpulan data, penyajian data, reduksi data dan kesimpulan yang dilakukan hingga data bersifat jenuh. Informan dalam penelitian ini yaitu kepala sekolah SMPN 3 Tulungagung, Wakil kepala bidang Kurikulum, guru IPS kelas 7.10, serta siswa kelas 7.10. Hasil penelitian menunjukkan upaya guru dalam meningkatkan karakter disiplin dan tanggung jawab pada diri peserta didik kelas 7.10 melalui kebijakan merdeka belajar dalam pembelajaran IPS yaitu: 1) menjadi tokoh teladan bagi peserta didik; 2) selalu mengutamakan kesepakatan kelas; 3) mengimplementasikan RPP yang bermuatan nilai-nilai karakter, menarik, berpusat kepada siswa; 4) selalu melakukan refleksi di akhir pembelajaran; dan 5) menjalin komunikasi yang baik dengan siswa dan wali murid. Peningkatan karakter disiplin dan tanggung jawab pada siswa kelas 7.10 terlihat pada beberapa hal misalnya kedatangan siswa, pelaksanaan piket kelas, penggunaan seragam dengan rapi, pemberian surat izin ketika tidak masuk. Sedangkan faktor pendukungnya dalam peningkatan tersebut diantaranya yaitu: terjalinnya komunikasi yang baik antar pihak guru dengan guru ataupun guru dengan kepala sekolah, lingkungan sekolah yang positif, lingkungan keluarga, motivasi dalam pembelajaran. Sedangkan faktor penghambatnya yaitu : dari pihak wali murid, kurangnya kolaborasi yang baik antara pengajar.